Bounded mixed batch scheduling with job release dates and rejection - Xu, Jun; Huang, Yong-Xing; Zhang, Daxing; Lin, Ran; Fan, Guo-Qiang (Operations research letters, 2024)
This paper investigates a bounded mixed batch scheduling problem with job release dates and rejection. The machine processes a batch containing several jobs that their number does not exceed the machine capacity. For the case with a certain release date, we present a polynomial-time exact algorithm. For the case with a constant number of release dates, a pseudo-polynomial-time exact algorithm is proposed. For the general problem, we provide a 2-approximation algorithm and a polynomial-time approximation scheme. •We investigate a bounded mixed batch scheduling problem with job release dates and rejection penalty.•We present a polynomial-time exact algorithm and a pseudo-polynomial time exact algorithm for two special cases.•For the general problem, we devise a 2-approximation algorithm and a polynomial-time approximation scheme.